Annealing behaviour of cold-rolled Cu–Ag alloy under mechanical loads. Issue 7 (3rd May 2018) - Lu, Yue; Ma, Ru; Wang, Yi-nong
ABSTRACT: The influence of the mechanical stress much lower than the yield stress during annealing on the annealing behaviour of cold-rolled Cu–Ag alloy was investigated. The optical microscopy, X-ray diffraction and electron backscatter diffraction (EBSD) were used to characterise the microstructure and texture. When such annealing of cold-rolled Cu–Ag alloy is conducted under uniaxial tensile stress, an analysis of the work hardening behaviour and microstructural evolution indicated that the presence of uniaxial tensile stress during annealing retards recrystallisation. EBSD studies also revealed that the dislocation density of the sample annealed under stress is lower than that after cold-rolled. The retardation of recrystallisation is associated with the reduction of the dislocation density of unrecrystallised cold-rolled Cu–Ag alloy induced by dynamic recovery.